Gemcitabine as adjuvant chemotherapy in patients with high-risk early breast cancer: results from the randomized phase III SUCCESS-A trial - De Gregorio, Amelie; Häberle, Lothar; Fasching, Peter A.; Müller, Volkmar; Schrader, Iris; Lorenz, Ralf; Forstbauer, Helmut; Friedl, Thomas W. P.; Bauer, Emanuel; de Gregorio, Nikolaus; Deniz, Miriam; Fink, Visnja; et al. (Breast cancer research, 2020)
When chemotherapy is indicated in patients with early breast cancer, regimens that contain anthracyclines and taxanes are established standard treatments. Gemcitabine has shown promising effects on the response and prognosis in patients with metastatic breast cancer. The SUCCESS-A trial (NCT02181101) examined the addition of gemcitabine to a standard chemotherapy regimen in high-risk early breast cancer patients.
Gesehen am 08.12.2020